Insecticide-treated net utilization and associated factors among pregnant women in East Africa: evidence from the recent national demographic and health surveys, 2011–2022 - Terefe, Bewuketu; Habtie, Adane; Chekole, Bogale (BioMed Central Ltd, 2023)
Abstract Background The pregnant woman, the fetus, and the newborn child are all at risk from malaria infection in subSaharan Africa. Employing insecticide-treated mosquito nets (ITNs) is one of the most efcient methods for avoiding malaria among expectant mothers. However, there is no literature that describes ITN use among pregnant women in East Africa or the contributing factors. Therefore, this study sought to identify the factors afecting pregnant women’s ITN utilization in East Africa. Methods The most recent DHS (Demographic and Health Survey) data for the 11 East African countries from 2011 to 2022 was used. 13,729 pregnant women were examined. To identify factors associated with ITN use, a binary and multiple logistic regression model was built. Variables having a p-value of less than or equal to 0.2 in the binary logistic regression analysis were taken into consideration for the multivariable analysis. In the multiple logistic regression analysis, the adjusted Odds Ratio (aOR) with the 95% Confdence Interval (CI) was provided to proclaim the statistical signifcance and degree of correlation. Results The survey found that just 47.05% (95% CI 46.21, 47.88) of pregnant mothers reported using ITNs. The highest and lowest values were seen in Uganda (64.13%) and Zimbabwe (6.08%). Women age 25-34y (aOR=1.19; 95% CI 1.11, 1.29), 35–49y (aOR=1.26; 95% CI 1.13, 1.41) as compared to 15–24 years, poorer (aOR = 1.15; 95% CI 1.04–1.27), middle (aOR=1.21; 95% CI 1.09, 1.35), and rich (aOR=1.18; 95% CI 1.06, 1.31) wealth indexes as compared to poorest, having>5 family size (AOR=0.84; 95% CI 0.78, 0.91) primary (aOR=1.49; 95% CI 1.36, 1.65), and secondary/higher education (aOR=1.52; 95% CI 1.35, 1.70) as compared to not educated, and married women (aOR=1.64; 95% CI 1.44, 1.86) have shown a statistically signifcant association with ITN utilization among pregnant women. Conclusion With a variety of risk variables, including age, wealth, family size, and education, pregnant women in East Africa rarely use ITNs. There is a need to create and strengthen malaria prevention programmes, especially among pregnant women who do not use ITNs, based on the variables mentioned. Keywords Insecticide-treated net, Pregnant women, East Africa
Keywords: Insecticide-treated net, Pregnant women, East Africa